QAZÍ MÁWLIK ShÍǴARMALARÍ TILINDE SINONIMLER - Karlıbaeva, G.; Orınbaeva, J. (SCIENCE and SOCIETY, 2025)
The article discusses the linguistic features of the works of the Karakalpak poet Qazi Mavlik, who lived in the 20th century. It examines the synonyms used in the poet‘s language and the characteristics of their application.